2001
DOI: 10.1046/j.1440-1622.2001.02125.x
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured abdominal aortic aneurysms: Clinical presentation in Auckland 1993–1997

Abstract: Although our ability to correctly diagnose a RAAA has improved since Osler's time, the initial misdiagnosis rate of 16% leaves no room for complacency. Ruptured abdominal aortic aneurysms must be included in the differential diagnosis of any patient over the age of 55 years who presents with shock, even if the pain is non-specific or atypical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 9 publications
1
19
0
1
Order By: Relevance
“…This study confirms previous findings that rAAA is commonly misdiagnosed across a range of settings [28]. rAAAs were mistaken for twelve different diseases in this series.…”
Section: Discussionsupporting
confidence: 92%
“…This study confirms previous findings that rAAA is commonly misdiagnosed across a range of settings [28]. rAAAs were mistaken for twelve different diseases in this series.…”
Section: Discussionsupporting
confidence: 92%
“…The methods of identifying prehospital deaths from rAAA differed widely and were frequently not described extensively. Some studies reviewed only prehospital deaths where diagnosis was confirmed at autopsy, whereas others determined the number of prehospital deaths as reported by the register of International Classification of Diseases. Overall, the autopsy rate of the population was poorly and inconsistently described ( Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies did not sufficiently describe the locations where patients with an rAAA died. The distribution according to location was therefore determined from the remaining 21 studies.…”
Section: Resultsmentioning
confidence: 99%
“…The authors, like their colleagues who reported from a large Auckland specialist centre, 4 emphasize the significance of blood loss which is > 3 L, is associated with a higher mortality, and the similar significance of prolonged operating theatre time. They did not, however, report the time lapse from rupture to operation and its effect on morbidity or mortality.…”
mentioning
confidence: 67%